PENGARUH TAX PLANNING DALAM UPAYA MENINGKATKAN KINERJA KEUANGAN - Indira Shinta Dewi shinta (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
This study aims to see the effect of tax planning in efforts to improve financial performance. Using the Tax Retention Rate, Book Tax Differences, and Effective Tax Rate proxies on how tax planning affects the financial performance of manufacturing companies in the pharmaceutical and consumer sub-sectors between 2019-2022, the Indonesia Stock Exchange is the object of data collection. Data processing uses Statistical Product and Service Solution for Windows version 24. Purposive sampling using several appropriate criteria was used to collect 175 data. Multiple regression analysis is a method of data analysis. The findings of the analysis show that the Tax Retention Rate, Book Tax Difference (BTD), Effective Tax Rate have an influence on efforts to improve financial performance. Based on the results of the F test, it also has an influence on efforts to improve financial performance